Natural Gas Policy Change in Mexico. The Political Economy of State Ownership and Regulation (1995-2018) - Aguirre Ponce, Rafael Armando (Université d'Ottawa / University of Ottawa, 2021)
A reform of the constitutional bases of the oil and gas industry in Mexico took place in 2013 (with sweeping changes to secondary legislation through 2014). Private and foreign production of hydrocarbons became legal after almost six decades of national monopoly --and 75 years after the revolutionary regime nationalized the assets of foreign producers. A wholesale market for electricity was also put in place. These legal reforms started to crystallize in 2018, as private producers started to have access to the networks carrying electricity and gas across the nation. This research presents a retrospective examination of 23 years of policy implementation in the natural gas industry of Mexico (1995-2018). The dissertation pays central attention to the patterns of state intervention that have characterized the national economy and that have contributed to shape the outcome of two policy packages pursuing liberalisation (one starting in 1995 and the other in 2013 and 2014). The research is based on a classical political economy approach, drawing on the literature on Varieties of Capitalism and Varieties of State Capitalism. The study centers on the relations between the players in the sector: their constraints and resources, against a backdrop of other economic policies affecting energy. Importantly, this study considers regulation as a mechanism of economic coordination. As a process-tracing case study, this thesis sets out to elucidate the distinctive factors that contributed to produce the current organization of the natural gas sector in Mexico --one where, ironically, liberalisation has been possible thanks to the deployment of a new state-owned enterprise. Three factors stand out as characteristic in the Mexican trajectory towards liberalisation: the strength of the national oil company as an obstacle of upstream liberalisation for almost two decades after 1995; the absence or weakness of constituencies supporting the restructuring of the sector (large industrial consumers, local distributors), and the sudden restructuring of supply and demand patterns, with the state-owned electricity enterprise emerging as a dominant trader. The new centrality of the electricity SOE and an Independent System Operator (also an SOE) underscores the limits of the new, more competitive, structure of the Mexican natural gas industry.
Keywords: Natural gas; energy; Regulation; Mexico; State-owned enterprises; Political Economy